Study Molecular Docking of pigment compounds derived from monascus sp as hepatitis B inhibitors - Anna Yuliana; Dikri Fadhlurrohman (MEDIA ILMU KESEHATAN, 2022)
Background: Pigment is a dye derived from the mold of Monascus sp which is known to have antiviral activity, hepatitis B is an inflammation of the liver organs caused by the hepatitis B virus. Objective: This study aims to find out whether the five pigments of Monascus sp derivative compounds have the potential to be inhibitors of hepatitis BMethods: The method used in this study is molecular docking, with hepatitis B virus protein samples with the PDB code 5GMZ to be used as docking targets. Results: The results of docking showed that monascin compounds had the best inhibitor activity with energy binding of -7.96 kcal / mol and an inhibition constant of 1.46 uM, the formation of hydrogen and hydropobic bonds.The results of the RMSD chart from MD showed that the Monascin compound was stable at the beginning of the simulation with an average RMSD of 2.1 Å, on the RMSF chart it showed the lowest fluctuation when the compound bound to the amino acid PHE103.Conclusion: Of the five test ligands used, the potential as an inhibitor of hepatitis B is the compound Monascin